Analisis Kelembagaan Terhadap Model Pembangunan Koperasi Berbasis Negara - Supriyono (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
Cooperative development in Indonesia has largely followed a state-based model aimed at strengthening the people’s economy. However, many cooperatives established through state intervention exhibit weak institutional capacity and limited sustainability. This study aims to critically analyze the state-based cooperative development model from an institutional perspective. A qualitative approach with an interpretive case study design was employed. Data were collected through in-depth interviews, observation, and document analysis, and analyzed thematically using institutional theory and elite theory. The findings indicate that strong state dominance produces administratively driven cooperatives characterized by low member participation, high dependence on government assistance, and vulnerability to local power relations. These results reveal a paradox in state-based cooperative development. The study concludes that strengthening cooperatives requires a shift in the role of the state from dominant controller to institutional facilitator that promotes autonomy and internal democratic governance.